2022
DOI: 10.54589/aol.35/1/25
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Demirjian method to estimate dental age in panoramic radiographs of patients treated at the Buenos Aires University School of Dentistry

Abstract: The aim of this study was to determine the difference between real age (RA) and dental age (DA) in boys and girls from the Autonomous City of Buenos Aires (C.A.B.A.) by analyzing digital panoramic radiographs from the database of the Imaging Department at the Buenos Aires University School of Dentistry, using the Demirjian Method (DM). The sample consisted of 508 panoramic radiographs of 6- to 14-year old Argentines (268 female and 240 male). The Demirjian method was used to estimate dental age from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The application of the London atlas of tooth development and eruption showed an average overestimation of age by only one month in the Portuguese population, although further studies are needed [51]. Applying the Demirjian method to samples of different nationalities has largely led to authors concluding on overestimation of dental age, although some studies have indicated underestimation [31,35,52]. Among the studies finding underestimation is that of Cruz-Ladeira et al [53] with Venezuelan subjects and that of Chen et al [54] with Chinese individuals, although underestimation only occurred in boys; this result agrees with the 11 to 12 age group in boys in this study, where the method pointed towards slight underestimation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of the London atlas of tooth development and eruption showed an average overestimation of age by only one month in the Portuguese population, although further studies are needed [51]. Applying the Demirjian method to samples of different nationalities has largely led to authors concluding on overestimation of dental age, although some studies have indicated underestimation [31,35,52]. Among the studies finding underestimation is that of Cruz-Ladeira et al [53] with Venezuelan subjects and that of Chen et al [54] with Chinese individuals, although underestimation only occurred in boys; this result agrees with the 11 to 12 age group in boys in this study, where the method pointed towards slight underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Simple and multiple linear regressions were used to obtain a parsimonious model, allowing estimation of chronological age from the measurements made of the seven teeth based on each method and the variables of sex and age group, since in previous studies the Demirjian method is shown to be sensitive to these variables [7,30,[35][36][37][38]. Using regression equations provides a more precise approach to chronological age based on Demirjian's staging method [43].…”
Section: Ethics Procedures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation